Inward-rectifying K+ (Kir2) leak conductance dampens the excitability of lamina I projection neurons in the neonatal rat. (17th December 2016) - Ford, Neil C.; Baccei, Mark L.
Highlights: Neonatal rat spino-PB and spino-PAG neurons express similar leak conductance through inward-rectifying K + (Kir ) channels. Block of Kir 2 channels significantly enhances the intrinsic membrane excitability of both spino-PB and spino-PAG neurons. Kir 2 channels may thus constitutively diminish nociceptive signal transmission from the neonatal spinal cord to the brain. Abstract: Spinal lamina I projection neurons serve as a major conduit by which noxious stimuli detected in the periphery are transmitted to nociceptive circuits in the brain, including the parabrachial nucleus (PB) and the periaqueductal gray (PAG). While neonatal spino-PB neurons are more than twice as likely to exhibit spontaneous activity compared to spino-PAG neurons, the underlying mechanisms remain unclear since nothing is known about the voltage-independent (i.e. 'leak') ion channels expressed by these distinct populations during early life. To begin identifying these key leak conductances, the present study investigated the role of classical inward-rectifying K + (Kir 2) channels in the regulation of intrinsic excitability in neonatal rat spino-PB and spino-PAG neurons. The data demonstrate that a reduction in Kir 2-mediated conductance by external BaCl2 significantly enhanced intrinsic membrane excitability in both groups. Similar results were observed in spino-PB neurons following Kir 2 channel block with the selective antagonist ML133. In addition, voltage-clamp experiments showed that spino-PB and spino-PAG neurons express similar amounts of Kir 2 current during the early postnatal period, suggesting that the differences in the prevalence of spontaneous activity between the two populations are not explained by differential expression of Kir 2 channels. Overall, the results indicate that Kir 2-mediated conductance tonically dampens the firing of multiple subpopulations of lamina I projection neurons during early life. Therefore, Kir 2 channels are positioned to tightly shape the output of the immature spinal nociceptive circuit and thus regulate the ascending flow of nociceptive information to the developing brain, which has important functional implications for pediatric pain.